Brief Report: Same-Sex Male Couples' Characteristics and Attitudes Toward Different HIV Prevention Services, by Dyad HIV Serostatus, in Lima, Peru. Issue 4 (2nd October 2019) - Mitchell, Jason; Brown, Shari; Pennington, Jacob; Wu, Yan Yan; Konda, Kelika
Abstract: Few HIV/STI prevention studies have been conducted with same-sex male couples in Lima, Peru. This brief report describes quantitative findings of 42 same-sex male couples' characteristics and attitudes towards using various HIV prevention services. Couples' communal coping and preferences for sexual health outcomes varied by their serostatus. Many partners were willing to use pre-exposure prophylaxis, couples HIV testing and counseling, and other couples-based prevention services, if and when they would become available. Partners' likelihood of using HIV prevention services differed by their dyadic serostatus. These findings lend support for providing couples-based HIV/STI prevention interventions for this population in Lima.